PENGARUH PENGGUNAAN APLIKASI CABRI 3D TERHADAP HASIL BELAJAR SISWA PADA MATERI BANGUN RUANG PRISMA DI SMP NEGERI 1 JORLANG HATARAN - Helen Ronauli Simanjuntak; Lois Oinike Tambunan; Golda Novatrasio Sauduran (MES: Journal of Mathematics Education and Science, 2022)
The purpose of this study was to determine whether the use of the 3D Cabri application had an impact on student learning outcomes in studying prisms of building materials or not. This research is quantitative research with experimental research methods and True Experimental Design in the form of a Pretest-Postest Control Design. This research was conducted at SMP Negeri 1 Jorlang Hataran. The samples used in this study were students of classes VIII-4 and VIII-8, each of which amounted to 32 people. The instrument used is an essay test with 5 items that have been tested for feasibility. Data collection techniques in research are through observation, tests, and documentation. The data analysis technique is using Liliefors test for the normality test, Fisher's test for the homogeneity test, and a t-test for hypothesis testing. After the two sample data are declared normal and homogeneous, it can be continued with hypothesis testing. From the results of data analysis, it was found that the use of Cabri 3D had an effect on student learning outcomes in the material of building prisms at SMP Negeri 1 Jorlang Hataran.